2019
DOI: 10.1001/jamadermatol.2018.4398
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Bidirectional Association Between Major Depressive Disorder and Alopecia Areata

Abstract: IMPORTANCE Alopecia areata (AA) is an autoimmune disease characterized by hair loss that can impose a substantial psychological burden on patients, including major depressive disorder (MDD), yet many patients report mental health symptoms prior to the onset of AA. As such, there may be an association between MDD and AA that acts in both directions.OBJECTIVE To assess the bidirectional association between MDD and AA. DESIGN, SETTING, AND PARTICIPANTSThis population-based retrospective cohort study included pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 13 publications
2
47
0
1
Order By: Relevance
“…Interestingly, people with depression without systemic inflammatory disorders have increased levels of inflammatory cytokines including tumour necrosis factor‐α and interleukin‐6, as is seen in psoriasis, thereby suggesting a potential for a shared inflammatory pathway. Recent evidence supports a link between depression and the subsequent development of other immune‐mediated disease . As depression has been demonstrated to have an influence on the disease course of psoriasis and increase the risk of psoriatic arthritis, we hypothesize that depression may also confer a heightened risk of developing psoriasis.…”
Section: Demographic Data At Baseline For the Depression And The Genementioning
confidence: 78%
“…Interestingly, people with depression without systemic inflammatory disorders have increased levels of inflammatory cytokines including tumour necrosis factor‐α and interleukin‐6, as is seen in psoriasis, thereby suggesting a potential for a shared inflammatory pathway. Recent evidence supports a link between depression and the subsequent development of other immune‐mediated disease . As depression has been demonstrated to have an influence on the disease course of psoriasis and increase the risk of psoriatic arthritis, we hypothesize that depression may also confer a heightened risk of developing psoriasis.…”
Section: Demographic Data At Baseline For the Depression And The Genementioning
confidence: 78%
“…A previous study demonstrated that dermatologists frequently underestimated the presence of mood disorders in patients with significant skin diseases [13]. In fact, there is extensive research indicating an increased risk of depression in patients with dermatological disorders such as psoriasis, alopecia areata, and atopic dermatitis [23][24][25]. Pemphigus may have a negative impact on the patients' body image [26].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a population-based retrospective cohort study identified a bidirectional association between major depressive disorder (MDD) and AA. Although patients with AA were found to have a risk of developing MDD, MDD was also found as a significant risk factor for AA development, mitigated through antidepressant prescription (Vallerand et al, 2019).…”
Section: Alopecia Areatamentioning
confidence: 99%
“…Although patients with AA were found to have a risk of developing MDD, MDD was also found as a significant risk factor for AA development, mitigated through antidepressant prescription(Vallerand et al, 2019). In a cross-sectional study examining the psychosocial effects of AA, signs of anxiety and depression, decreased quality of life, and suicide risk were found in a sample of 126 patients (Vélez-Muñiz, Peralta-Pedrero, Jurado-Santa Cruz, & Morales-Sánchez, 2019).…”
mentioning
confidence: 99%